Optical Quality Assessment in Patients with Unilateral Congenital Ptosis: A Matched Case-Control Study. (17th November 2020) - Shen, Jianqin; Cui, Hongguang; Tang, Xuyuan; Zhu, Miaomiao; Han, Wei
Abstract : Background . To evaluate the differences in the corneal higher-order aberrations (HOAs) and optical quality of the ptosis eyes compared with the normal fellow eyes in the unilateral congenital ptosis patients. Methods . A matched case-control study was performed in 17 pairs of eyes in 17 unilateral congenital ptosis patients. The ptosis eye was enrolled in the ptosis group while the normal fellow eye was enrolled in the normal group. The HOAs obtained from Pentacam HR and the optical quality parameters obtained from Optical Quality Analysis System (OQAS) were compared between the two groups. Results . There were significant differences in a vertical coma and vertical trefoil on the anterior corneal surface between the ptosis group and the normal group p < 0.05 . The OQAS parameters in the ptosis group were significantly different from those in the normal group p < 0.05 . The vertical fissure height (VFH) showed a significant correlation with the total HOAs, 3 rd HOAs, and vertical coma on the anterior corneal surface p < 0.05 . Conclusions . Compared with the normal fellow eyes, the ptosis eyes showed significantly degraded optical quality. The eyelid position was important for the changes of corneal HOAs in the ptosis eyes. The reasons for the discrepancy of the OQAS parameters between the ptosis eyes and normal fellow eyes were multiple.